(untitled) (Economic and Political Thought, 2010)
The aim of the present work is to present selected views of specialists in financial law and economics on the desired shape taxation system, especially corporate income tax. The author tries to do this in a clear way for lawyers and economists as well as laypersons. Firstly, the article discusses some demands for the taxation system made by economists and presents short-term effects of taxation policy based on the IS-LM model. Next, it presents selected opinions of the financial law doctrine on income tax, especially corporate income tax. The article also contains a description of selected institutions of American tax law and some proposals to make use of American experiences in Poland. The article is an attempt to take a wide approach to the issue of income tax, especially corporate income tax, including economic opinions as well as fiscal and legal views. Such a broad approach to the issue is a result of a conviction that issues connected with taxation lie on the meeting ground for interests of two sciences which seem to be very distant from each other: law and economics.